Etika Birokrasi Dalam Meberikan Pelayanan Publik - Murniyati Yanur (Jurusan Ilmu Pemerintahan, 2023)
Governance is aimed at creating quality public service functions. Quality public services are services that can provide satisfaction to the public. This can be seen from the 5 dimensions of public service quality which are the benchmarks in providing satisfaction to the community, namely, reliability, responsiveness, assurance, empathy, and tangibles. The ethical standards of public service required here are the fulfillment or embodiment of the values or norms of attitude and behavior of the public bureaucracy in every service and action, which can be accepted by the wider community. This does not mean that the public service bureaucracy does not have service ethical standards at all, but it is the application of these ethics that may need to be improved. The method used in this research is qualitative with a literature study. The result of this study is that the existence of a code of ethics does not guarantee that the public service bureaucracy in Indonesia becomes an efficient, clean, and accountable bureaucracy. What is important is not just the existence of rules that are formulated in detail what are the ethical values of administrators but how these values are implemented. Two very important things in implementing ethics are the existence of standards (rules or norms) that must be obeyed and a strong will to carry them out.